Pola Perubahahan Beberapa Sifat Morfologis dan Fisiologis Buah Kelapa Sawit - Harahap, Lukman Syaidy; Rasyad, Aslim; Isnaini, Isnaini; Khoiri, Muhammad Amrul (Jurnal Agro Teknologi Tropika, 2016)
This study attempted  to determine the change of  morphological and  physiological traits of fruit palm oil during the fruit development until harvest. Forty eight fruit bunchs which antheses at the same day were selected at random from oil palm trees in the Experimental Station of PT Panca Surya Garden at Kubang Raya, Kampar. The fruit bunches were hand pollinated at 18 April 2015 and each was covered by pollination bag. Starting at 30 days after pollination (DAP), 3 fruits bunches were harvested at 15 day interval until fruits were ready to harvest. The change of morphological and physiological traits were observed  such as fresh weight, dry weight, fruit moisture content, thickness of mesocarp, fruit diameter, fruit volume and fruit color. The data analysis were performed by simple regression assingned day after pollination as independent variable and the traits observed as dependent variables.  The results indicated that change in morphological traits such as mesocarp thickness, fruit volume, fruit diameter occurred in similar pattern. Rapid change of  the value appeared from 30 to 75 DAP, followed by very slow increased from 75 to 150 DAP and finally the  rapid increase from 150 to 180 DAP. The pattern of dry weight and fresh weight change was similar, in which progressive increase was occurred  from 30 to 180 DAP then followed by decreased until 187 DAP. Moisture concentration of the fruit increased slightly from 30 to 45 DAP than decreased progressively from 45 to 187 DAP. Fruit color changed from dark purple to red purple and finally at harvest the color change to yellow red.